The Sharia and Islamic public law in time of war and peace - Bassiouni, M. Cherif (Cambridge University Press, 2014)
This innovative and important book applies classical Sunni Muslim legal and religious doctrine to contemporary issues surrounding armed conflict. In doing so it shows that the shari'a and Islamic law are not only compatible with contemporary international human rights law and international humanitarian law norms, but are appropriate for use in Muslim societies.